2005
DOI: 10.1097/01.pas.0000151617.14598.ae
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hyperinsulinemic Hypoglycemia in 15 Adults With Diffuse Nesidioblastosis

Abstract: Persistent hyperinsulinemic hypoglycemia (PHH) in adults that is not caused by an insulinoma is a rare and not well-characterized disease that has been named nesidioblastosis. In this study, we defined and scrutinized criteria for its histologic diagnosis, assessed its relative incidence, and discussed its pathogenesis. In pancreatic specimens from 15 adult patients with PHH in whom no insulinoma was detected and in 18 adult control patients, the endocrine tissue was screened for islet and beta-cell changes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 27 publications
4
85
1
3
Order By: Relevance
“…It was therefore proposed that the hyperinsulinemic hypoglycemia was likely secondary to this presumed excessive concentration of GLP-1 (5). In support, in vitro and animal studies reported that GLP-1 may increase ␤-cell replication and inhibit ␤-cell apoptosis (6,7), and it has been reported that GLP-1 concentrations are increased after GBS (8 -10).Hyperinsulinemic hypoglycemia has been reported both in infants (11,12) and more rarely in adults (13,14) in the absence of insulinoma. In infants, this condition was originally termed nesidioblastosis (15) as it was thought that the hyperinsulinemia arose as a consequence of increased islet formation from putative islet precursors adjacent to pancreatic ducts.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…It was therefore proposed that the hyperinsulinemic hypoglycemia was likely secondary to this presumed excessive concentration of GLP-1 (5). In support, in vitro and animal studies reported that GLP-1 may increase ␤-cell replication and inhibit ␤-cell apoptosis (6,7), and it has been reported that GLP-1 concentrations are increased after GBS (8 -10).Hyperinsulinemic hypoglycemia has been reported both in infants (11,12) and more rarely in adults (13,14) in the absence of insulinoma. In infants, this condition was originally termed nesidioblastosis (15) as it was thought that the hyperinsulinemia arose as a consequence of increased islet formation from putative islet precursors adjacent to pancreatic ducts.…”
mentioning
confidence: 83%
“…As a consequence, this syndrome was renamed persistent hyperinsulinemic hypoglycemia of infancy (17). Recent studies of pancreata of adults with hyperinsulinemic hypoglycemia in the absence of an insulinoma have revealed that the most striking abnormality is hyperplastic ␤-cells with enlarged nuclei, consistent with chronically increased insulin secretion, analogous to persistent hyperinsulinemic hypoglycemia of infancy (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, these patients have islet enlargement, hypertrophic b-cells with enlarged hyperchromatic nuclei and abundant clear cytoplasm (17,20). The detailed histology of the six cases reported by Service et al was reanalysed subsequently using a different control group from autopsy specimens (7,17).…”
Section: Discussionmentioning
confidence: 99%
“…Nesidioblastosis affects approximately 4% of adults with hyperinsulinemic hypoglycemia [9]. The role of imaging is first to detect and provide precise anatomical localization and second to stage the tumor prior to surgery.…”
Section: Diagnostic Procedures: Clinical Assessment With Laboratory Tmentioning
confidence: 99%